The impact of accession to GATT on trade-related policies of CIS countries: the case of Belarus - Matthias Lücke (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
This paper investigates which policies CIS countries need to reform when they accede to GATT. The objectives to be pursued through trade policy (e.g. raising fiscal revenue, protecting industries, regional integration) must be defined clearly when tariff levels are bound. Some streamlining (e.g. tariffication of export quotas) is also required. The format of regional integration with Russia (free trade area vs. customs union with joint GATT membership) must not discriminate against GATT contracting parties, and will be influenced by whether Russia is willing to export energy at its low domestic price. Furthermore, systemic reforms need to be accelerated to dispel concerns about discrimination against imports, or hidden subsidies for exports.
Keywords: F14; F15; 330; General Agreement on Tariffs and Trade; CIS countries; Belarus; trade policy reform